Green Human Resource Management, Sustainable HRM, dan Green Training Terhadap Organizational Sustainability: Systematic Literature Review (SLR) - Rhifwan Aji; Zahara Tussoleha Rony; Bimantoro Adriyanto (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Growing concerns regarding sustainability have encouraged organizations to integrate human resource management practices that simultaneously address economic, social, and environmental dimensions. This study aims to examine the influence of Green Human Resource Management (GHRM), Sustainable Human Resource Management (Sustainable HRM), and Green Training on Organizational Sustainability through a Systematic Literature Review (SLR). The review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, including identification, screening, eligibility assessment, and synthesis of relevant studies retrieved from Google Scholar, Scopus, ScienceDirect, SpringerLink, Emerald Insight, and Taylor & Francis published between 2021 and 2025. Eligible articles were analyzed using descriptive and thematic synthesis to identify research trends, relationships among variables, and existing research gaps. The findings indicate that Green Human Resource Management enhances environmentally responsible employee behavior, operational efficiency, and organizational sustainability culture. Sustainable Human Resource Management contributes to long-term organizational sustainability by promoting employee well-being, competency development, and sustainable value creation. Furthermore, Green Training improves employees' environmental knowledge, skills, and pro-environmental behaviors, thereby strengthening the implementation of sustainability strategies. Overall, the review demonstrates that these three human resource management practices positively contribute to Organizational Sustainability. This study enriches the theoretical development of sustainable human resource management literature and provides practical implications for organizations in designing strategic HR policies to achieve long-term organizational sustainability.